'Lonely and Voiceless Your Halls Must Remain': Romantic‐Era National Song and Felicia Hemans's Welsh Melodies (1822). (5th May 2014) - Edwards, Elizabeth
Abstract This article places Felicia Hemans's little‐discussed song collection A Selection of Welsh Melodies (1822) in the expanding field of eighteenth‐ and early nineteenth‐century national melody in Britain. Drawing on recent studies of Romantic paratext, it discusses the layered, contingent and interstitial nature of Welsh Melodies, via a series of close readings of the song texts. It argues that Hemans's approach to Wales in her songs reveals the collaborative and translational nature of her work, involving cultural and historical transmission, as well as the models of female subjectivity, professional authorship and (at times) feminist sentiment for which she is better known.